(untitled) - Prentic, William E. (Boston, 1999)
The sixth edition of Fitness and wellness for life is designed to provide a comprehensive, readable text for use in general fitness and wellness classes that are designed to acquaint college students with the nature and scope of healthy living. The text emphasizes the value of establishing lifelong patterns of fitness and healthy living. It provides individuals with facts and principles that form the basis for motivating people to incorporate some form of physical activity into their daily lives.
Keywords: Physical fitness,Thể dục thể chất